Families of choice with no choice: remarks concerning the situation of families of choice in Polish law. (31st March 2023) - Drapalska-Grochowicz, Marlena
Abstract: This article focuses on the situation of families of choice in Polish law. The first research objective was to determine whether and how parenting in families of choice is regulated by law. To achieve this goal, the author analysed appropriate statute and case law, taking into account the sociological and psychological background of family relationships. The second objective was to find legal and non-legal factors affecting the current situation of families of choice in Polish law. Then it was assessed whether it is possible to provide court protection to the families of choice in the process of applying current regulations. This article shows that although the Polish legislator considers family life an important value, it is restricted to a specific understanding of family. Neither the Polish legislator nor the legal discourse recognize the needs of the families of choice, and the chances of changing the current situation are small.